PENGARUH TOILET TRAINING TERHADAP KEMANDIRIAN ANAK USIA 3-4 TAHUN DI KB KARTIKA KEPUNDUNGAN SRONO BANYUWANGI TAHUN PELAJARAN 2018-2019 - Hasanah, Ifatul; Putri, Ellyana Ilsan Eka; Bahari, John Iskandar (Institut Agama Islam Ibrahimy Genteng Banyuwangi, 2019)
Based on preliminary observations at KB Kartika, it was found that the independence of toileting at KB Kartika was still quite low. Considering the importance of self-reliance in toilet and considering the potential that based on PERMENDIKBUD No. 137 of 2014 children aged 3-4 years have been able to say 5-6 words, this study takes the formulation of the problem of how the influence of toilet training on the independence of children aged 3-4 years in KB Kartika Kepundungan Srono Banyuwangi. The purpose of this study was to determine how the influence of toilet training on the independence of children aged 3-4 years in KB Kartika Kepundungan srono Banyuwangi. This type of research used in this study is field research, which is a study of the reality of people's social lives directly. Data analysis uses data reduction, data presentation, and conclusions. The validity of the data uses triangulation of techniques and sources. The results of this study are that there is an influence of toilet training on the independence of the toilet of children aged 3-4 years at KB Kartika under the Srono Banyuwangi. The improvement that occurs every child is different. However, overall all children experience an increase in independence after toilet training.